2007
DOI: 10.1007/s10230-007-0153-7
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Groundwater Rebound in the South Yorkshire Coalfield, UK

Abstract: The semi-distributed model GRAM (groundwater rebound in abandoned mineworkings) has been applied to part of the South Yorkshire Coalfield, UK, to predict the pattern of groundwater rebound, in particular the timing and rates of changes in mine water flows between abandoned collieries. The model is based upon the mining hydrogeologist's concept of 'ponds' (discrete volumes of interconnected workings) and calculates water balances over time for all ponds in a multi-pond mined system. GRAM was successfully calibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 2 publications
0
24
0
1
Order By: Relevance
“…Underground Water Survey" (NCB 1964). The latter provided water level data 'before rebound' with the assumption that the water level did not change significantly between 1964 and the beginning of the simulations (1968) (personal comm., Younger 2006 ). An additional significant source of data was a report by the local water authority "Report on survey of water resources" (Northumbrian River Authority 1973).…”
Section: Conceptual Modelmentioning
confidence: 93%
“…Underground Water Survey" (NCB 1964). The latter provided water level data 'before rebound' with the assumption that the water level did not change significantly between 1964 and the beginning of the simulations (1968) (personal comm., Younger 2006 ). An additional significant source of data was a report by the local water authority "Report on survey of water resources" (Northumbrian River Authority 1973).…”
Section: Conceptual Modelmentioning
confidence: 93%
“…Again, the contrast with coal mines is telling -they generally ARE inter-connected all the way back to outcrop, and that is why we get significant water discharges from them (e.g. Kortas and Younger 2007;Gandy and Younger 2007); it is also noteworthy that once mine workings are drowned by rising groundwaters, any release of methane from them abruptly ceases (e.g. Hall et al 2005; Younger 2014) -there is no reason why depleted unconventional gas reservoirs should behave any differently when groundwater heads within them recover.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Younger et al 1995;Sherwood and Younger 1997;Burke and Younger 2000;Adams and Younger 2001;Whitworth 2002;Boyaud and Therrien 2004;Winters and Capo 2004;McCoy et al 2006;Gandy and Younger 2007;Hamm et al 2008;Kortas and Younger 2007;Light and Donovan 2015). Post-audits of these applications have shown that they produce useful and realistic results, and that engineering design decisions based on their application have stood the test of time (Younger, 2004;Adams 2014).…”
Section: Existing Approachesmentioning
confidence: 99%
“…Post-audits of these applications have shown that they produce useful and realistic results, and that engineering design decisions based on their application have stood the test of time (Younger, 2004;Adams 2014). For instance, the modelling study reported by Gandy and Younger (2007) was undertaken as part of a financial due diligence process during the sale of a profitable mine as a going concern, leading to extension of the life of the mine by eight years.…”
Section: Existing Approachesmentioning
confidence: 99%
See 1 more Smart Citation